The Portuguese programme one laptop per child: political, educational and social impact - Pereira, Sara (2015)
In 2008, the XVII Portuguese Constitutional Government launched the ‘e.escolinha’ programme, within the Technological Plan for Education, which set out the distribution of a computer, called ‘Magalhães’, designed for chil-dren attending the 1st cycle of basic education. Suspended in 2011 by the XIX Government, this programme has allowed, however, almost 500 000 children to have access to a personal computer. It was expected that this political measure would “revolutionise” the national education system by bringing changes to the pedagogical practices of teachers and the learning processes of children and by achieving educational success, in general. Based on documental analysis and on a set of interviews with key decision-makers in conceiving, implementing and monitoring this governmental initiative, the ﬁ rst part of this chapter presents and analyses the ‘e.escolinha’ initiative and the policies be-hind that governmental programme, seeking to disassemble those objectives and provide some insights into the relationship between discourses, rhetoric, and reality. After that, the chapter focuses on children’s uses and practices with the ‘Magalhães’ laptop, at school and at home. Based on the results of questionnaires ﬁ lled in by approximately 1500 children from 32 First Cycle public schools of the municipality of Braga (north of Portugal) and also from questionnaires applied to their parents and teachers, this chapter intends to analyse the real impact of this initiative for children, family and school. It also seeks to discuss the contribution of this educational policy to children’s digital literacy and also to their own and their families’ social and digital inclusion. To understand if it represented an added value to teachers’ pedagogical practice is another of its aims. The ﬁ ndings point out a major focus on technology and access rather than on uses and competences or even on social, educational and cultural change. In fact, a major conclusion is the existence of a strong gap between the policy and the practices, typical of a top-down policy design.